Reactive flash sintering of the complex oxide Li0.5La0.5TiO3 starting from an amorphous precursor powder. (February 2020) - Avila, Viviana; Yoon, Bola; Ingraci Neto, Rubens R.; Silva, Ronaldo S.; Ghose, Sanjit; Raj, Rishi; Jesus, Lílian M.
Abstract: We report the transformation of an amorphous mixture of Li0.5 La0.5 TiO3 (LLTO) directly into a single phase dense polycrystal, all within a few seconds at about 800  °C by the flash method. The starting material is a chemically-prepared precursor powder that experiences concurrent crystallization and densification to cubic LLTO during the flash event, as shown by in-situ X-ray measurements. The experiments were conducted at a constant heating rate with fields from 80 to 120 V cm −1 and a current limit of 60 mA mm –2 . The resulting polycrystal yielded a bulk conductivity of 0.5 mS cm –1 . Graphical abstract: Image, graphical abstract